Hukum Akad dan Investasi pada Asuransi dalam Perspektif Fikih Muamalah - Kisanda Midisen (Jurnal Ilmiah Ekonomi Islam, 2023)
This article aims to analyze the perspective of Muamalah's fiqh regarding the combination of several contracts in insurance and the investment system applied to insurance companies. Theoretically, there are different views of the Ulama in terms of the permissibility of combining several contracts in one transaction, there are scholars who think it is permissible, and there are scholars who prohibit combining contracts, including combining contracts in insurance. And how should the investment system run in insurance products that are in accordance with sharia principles. This research is qualitative research of literature with descriptive analysis method. The results of the study show that combining several contracts in insurance is permitted by Islamic scholars, and the investment system implemented by insurance companies is different between sharia insurance and conventional insurance.